2001
DOI: 10.1046/j.0022-202x.2001.01379.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the αvβ6 Integrin Promotes Migration and Invasion in Squamous Carcinoma Cells

Abstract: The integrin alphavbeta6 is a fibronectin receptor whose expression is not detectable on normal oral epithelium but is increased significantly in healing and in oral epithelial dysplasia and oral squamous cell carcinoma, suggesting it may promote changes associated with tumor development. To study whether alphavbeta6 may drive invasive behavior we have used transfection and retroviral infection to create a panel of epithelial cell lines expressing various levels of alphavbeta6. We report that increased express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
139
1
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 122 publications
(148 citation statements)
references
References 56 publications
6
139
1
2
Order By: Relevance
“…This observation is in accordance with various studies that have reported the role of integrin β 6 in mediating metastasis 15, 34, 35. However, as indicated on the graph (Fig.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This observation is in accordance with various studies that have reported the role of integrin β 6 in mediating metastasis 15, 34, 35. However, as indicated on the graph (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…In an evolving tumor, the stromal cues bring about changes in the extracellular matrix leading to activation of a family of integrins that mediate attachment of tumor cells to the extracellular matrix (ECM) 13. Components of the ECM, like fibronectin and tenascin and the latency‐associated peptide 1 and 3 have been shown to activate α v β 6 integrin leading to local activation of TGF β 1 signaling at tumor‐stroma interface facilitating tumor migration and invasion 14, 15, 16, 17.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, ␣v␤3 and ␣v␤6 could be the targets because both of them act as the important receptors for fibronectin, and both of them are deeply implicated in the promotion of the cancer cell metastasis (52)(53)(54)(55). One more important molecule that could not be ignored is E-cadherin, which plays critical roles in cell-cell adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…A panel of three oral SCC cell lines were used. We generated the invasive VB6 cell line previously by transfection and retroviral infection of integrin subunits to express high levels of the integrin avb6 (Thomas et al, 2001b). CA1 and 5PT were kind gifts from Professor IC Mackenzie (Cardiff dental School, UK).…”
Section: Cell Culturementioning
confidence: 99%